2013
DOI: 10.1103/physrevb.88.085130
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic electrical properties of LuFe2O4

Abstract: We here revisit the electrical properties of LuFe 2 O 4 , compound candidate for exhibiting multiferroicity. Measurements of dc electrical resistivity as a function of temperature, electric-field polarization measurements at low temperatures with and without magnetic field, and complex impedance as a function of both frequency and temperature were carried out in a LuFe 2 O 4 single crystal, perpendicular and parallel to the hexagonal c axis, and in several ceramic polycrystalline samples. Resistivity measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…In this way, for LuFe 2 O 4 and YFe 2 O 4 , below T CO , different fractional charges are localized in the lattice giving rise to an ordered sequence of charges, and larger discontinuities are observed in the crystal structure. On the contrary, a random distribution [59] or an incommensurate ordering seems to occur for the YbFe 2 O 4 compound [16], which remains in the hexagonal crystallographic structure even at low temperatures. Finally, the local structure instability should have an important role in the electrical properties, but their correlation with the kind of charge order is a matter of future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, for LuFe 2 O 4 and YFe 2 O 4 , below T CO , different fractional charges are localized in the lattice giving rise to an ordered sequence of charges, and larger discontinuities are observed in the crystal structure. On the contrary, a random distribution [59] or an incommensurate ordering seems to occur for the YbFe 2 O 4 compound [16], which remains in the hexagonal crystallographic structure even at low temperatures. Finally, the local structure instability should have an important role in the electrical properties, but their correlation with the kind of charge order is a matter of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, the claimed colossal dielectric constants are spurious effects originating from the electrical contacts [37][38][39], and on the other hand, LuFe 2 O 4 does not show spontaneous electrical polarization, as has been proved by electrical polarization measurements [39]. Although the occurrence of ferroelectricity can be discarded in LuFe 2 O 4 , the structural phase transition at T CO 320 K is still considered to originate from Fe 3+ /Fe 2+ CO. Resonant x-ray scattering (RXS) experiments at the Fe K-edge of the principal observed superstructure (1/3, 1/3, half-integer) reflections seem to support this assumption, but the analysis performed by either Ikeda et al [7] or Mulders et al [40] are merely qualitative, using a generic structure factor without considering any charge order sequence.…”
Section: Introductionmentioning
confidence: 99%
“…All the samples show a sharp transition at T N ≈ 250−240 K for H = 0.1 T (not shown here), in agreement with the expected ferrimagnetic ordering and a large low temperature coercivity. Thermal and electrical properties as a function of temperature for the studied RFe 2 O 4 (R = Lu, Yb, Tm, Y) samples show the anomalies at the phase transition temperatures expected for stoichiometric compounds [10,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread belief in the existence of ferroelectricity in LuFe 2 O 4 , recent results have challenged both the polar character and the existence of pure ionic CO. It has been demonstrated that the colossal dielectric permittivity is originated by the electrical contacts [39][40][41] and that LuFe 2 O 4 does not show spontaneous electrical polarization in the P (E) loops [41]. In addition, x-ray absorption spectroscopy (XAS) experiments at the Fe K edge have shown that the charge segregation between the different iron atoms cannot be larger than 0.5 electrons [42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation